Sugarcane Bagasse as a Carrier for the Immobilization of Saccharomyces cerevisiaein Bioethanol Production - Anita, Sita Heris; Mangunwardoyo, Wibowo; Yopi, Yopi (UI Scholars Hub, 2016)
Sugarcane bagasse was used as a carrier to immobilize Saccharomyces cerevisiae in bioethanol production. This research aims to study the potential use of sugarcane bagasse as an alternative carrier for cell immobilization and improvement in the production process of cell immobilization in bagasse. The results showed that the physical characteristics of sugarcane bagasse as a carrier were water content (7.77 ± 0.35%), water retention (4.80 ± 0.44 g/g), water absorption index (8.58 ± 0.22 g/g), and lignin content (24.40 ± 1.52 %). Determination of cell retention was performed in an inoculum volume of 50 mL yeast suspension with various carrier weights (2.5, 5, 10, and 20 g). The highest cell retention was obtained in ratio of 2.5 g carrier/50 mL cell suspension with cell retention of 5.41 ± 1.06 mg/g, or known as biocatalyst. Biocatalyst, as much as 1.5, 3, 4.5, and 6 g, were used as inoculum for a 24 hour bioethanol fermentation. The best concentration and productivity of bioethanol, obtained by using 3 g of biocatalyst, were 23.95 ± 0.28 g/L and 1.24 ± 0.01 g/L/hours. The average of bioethanol yield for a 24 hour fermentation by using immobilized cells was three times higher than the free cells system.